M*A*S*H. Season six [videorecording (DVD)] - Alda, Alan, 1936-; Farrell, Mike; Swit, Loretta; Morgan, Harry, 1915-2011; Stiers, David Ogden; Burghoff, Gary; Farr, Jamie, 1934-; Christopher, William, 1932-2016; Metcalfe, Burt; Gelbart, Larry (20th Century Fox Home Entertainment, 2008)
The adventures continue for the doctors and nurses of the 4077th unit during the Korean War.